Expansionary Austerity New International Evidence - Leigh, Daniel (IMF Working Papers; Working Paper ;, 2011)
This paper investigates the short-term effects of fiscal consolidation on economic activity in OECD economies. We examine the historical record, including Budget Speeches and IMFdocuments, to identify changes in fiscal policy motivated by a desire to reduce the budget deficit and not by responding to prospective economic conditions. Using this new dataset, our estimates suggest fiscal consolidation has contractionary effects on private domestic demand and GDP. By contrast, estimates based on conventional measures of the fiscal policy stance used in the literature support the expansionary fiscal contractions hypothesis but appear to be biased toward overstating expansionary effects.